Assessment of the constructability of the solutions for built-up roofs on profiled flooring with the account for the minimum thermal requirements. - Khokhrіakova, D.; Shamrina, G. (Ways to Improve Construction Efficiency, 2019)
The classification of the built-up roof constructive solutions by the profiled flooring has been proposed. The field of research was limited by the following options for constructive-technological solutions: with polymer membrane roof covering; with polymer membrane roof covering and combined insulation; with two-layer roof covering and sheet-backed coat from asbestos-cement plates; with a profiled flooring roofing. The thickness of the roof insulation layer was determined as that of thermally inhomogeneous structures in accordance with the minimum requirements of DBN V.2.6-31: 2016. The labor inputs and the roofing installing cost for accepted options were determined in accordance with RECN. Based on the research findings, the option of roofing on profiled flooring with a polymer membrane covering and combined insulation has been defined as the most rational.